2004
DOI: 10.1081/ese-200026331
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Environmental Exposure to Cadmium on Pregnancy Outcome and Fetal Growth: A Study on Healthy Pregnant Women in China

Abstract: The objective of the present study was to evaluate the potential effect of environmental exposure to cadmium on pregnancy outcome and fetal growth. Normal pregnant women were selected from Da-ye city of Hubei province, a cadmium-polluted area, from November 2002 through January 2003. Whole blood of pregnant women, cord blood, and placenta were collected and cadmium levels were determined by inductively coupled plasma emission mass spectroscopy. Incidence rate of preterm labor (gestational age < or = 37 weeks) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(51 citation statements)
references
References 18 publications
(21 reference statements)
3
44
3
Order By: Relevance
“…Even at term, adult mortality is associated with earlier delivery (Crump et al, 2011). Investigators have described associations between background exposures to toxic and essential elements in pregnant women and birth outcomes (Al-Saleh et al, 2014; Gundacker et al., 2010; Kippler et al, 2012a; Kippler et al, 2012b; Kozikowska et al, 2013; Lee et al, 2010; Lin et al, 2011; Menai et al, 2012; Shirai et al, 2010; Tian et al, 2009; van Wijngaarden et al, 2014; Zhang et al, 2004). However, there are few data to assess the impact of preconception exposures; measurements made during pregnancy are subject to within-woman variability concurrent to gestation-related physiologic adaptations (Selevan et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Even at term, adult mortality is associated with earlier delivery (Crump et al, 2011). Investigators have described associations between background exposures to toxic and essential elements in pregnant women and birth outcomes (Al-Saleh et al, 2014; Gundacker et al., 2010; Kippler et al, 2012a; Kippler et al, 2012b; Kozikowska et al, 2013; Lee et al, 2010; Lin et al, 2011; Menai et al, 2012; Shirai et al, 2010; Tian et al, 2009; van Wijngaarden et al, 2014; Zhang et al, 2004). However, there are few data to assess the impact of preconception exposures; measurements made during pregnancy are subject to within-woman variability concurrent to gestation-related physiologic adaptations (Selevan et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Animal studies have demonstrated reproductive and teratogenic effects. Small epidemiologic studies have noted an inverse relationship between cadmium in cord blood, maternal blood or maternal urine and birth weight and length at birth [127, 128]. …”
Section: Cadmiummentioning
confidence: 99%
“…This is because iAs can readily cross the placenta (Concha et al, 1998) and Cd, while doing so less readily, also crosses the placenta (Iyengar and Rapp, 2001; Zhang et al 2004). Epidemiologic studies support relationships between chronic iAs exposure and increased risk of spontaneous abortion, stillbirth, preterm birth, and neonatal death in pregnant women (Ahmad et al, 2001; von Ehrenstein et al, 2006; Rahman et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In pregnant women, Cd accumulation in the placenta causes inhibition of trophoblastic invasion, decreased steroidogenesis, and adjusted handling of nutritive essential metals that are deleterious to fetal and maternal health ( reviewed by Estaban-Vasallo et al, 2012). Consequently, Cd exposure has been associated with birth outcome effects such as lower birth weight and decreased birth height (Salpietro et al, 2002; Chisolm & Handorf, 1996; Zhang et al, 2004). …”
Section: Introductionmentioning
confidence: 99%